Partially hydrolysed guar gum ameliorates murine intestinal inflammation in association with modulating luminal microbiota and SCFA. Issue 7 (8th September 2016) - Takagi, Tomohisa; Naito, Yuji; Higashimura, Yasuki; Ushiroda, Chihiro; Mizushima, Katsura; Ohashi, Yuji; Yasukawa, Zenta; Ozeki, Makoto; Tokunaga, Makoto; Okubo, Tsutomu; Katada, Kazuhiro; Kamada, Kazuhiro; et al.
Abstract: Partially hydrolysed guar gum (PHGG), a water-soluble dietary fibre produced by the controlled partial enzymatic hydrolysis of guar gum beans, has various physiological roles. This study aimed to elucidate the beneficial effects of PHGG on colonic mucosal damage in a murine 2, 4, 6-trinitrobenzene sulfonic acid (TNBS)-induced colitis model. Acute colitis was induced in male C57BL/6 mice with TNBS after 2 weeks of pre-feeding with PHGG (5 %). The colonic mucosal inflammation was evaluated using macroscopic damage scores, and neutrophil infiltration was assessed by measuring tissue-associated myeloperoxidase (MPO) activity in the colonic mucosa. TNF- α expression in the colonic mucosa was measured by ELISA and real-time PCR. Moreover, the intestinal microbiota and production of SCFA were assessed by real-time PCR and HPLC, respectively. Colonic damage due to TNBS administration was significantly ameliorated by PHGG treatment. Furthermore, PHGG significantly inhibited increases in MPO activity and TNF- α protein and mRNA expression in the colonic mucosa in TNBS-induced colitis. On analysis of intestinal microbiota, we found that the concentration of the Clostridium coccoides group ( Clostridium cluster XIVa), the Clostridium leptum subgroup ( Clostridium cluster IV) and the Bacteroides fragilis group had significantly increased in PHGG-fed mice. On analysis of SCFA, we found that the caecal content of acetic acid, propionic acid and butyric acid had significantly increased in PHGG-fed mice. Together, these results suggest that chronic ingestion of PHGG prevents the development of TNBS-induced colitis in mice by modulating the intestinal microbiota and SCFA, which may be significant in the development of therapeutics for inflammatory bowel disease.